ANALISIS PENGARUH HARGA DAN KUALITAS LAYANAN TERHADAP KENYAMANAN DAN DAMPAKNYA PADA KEPUASAN KONSUMEN PADA BENGKEL DELTA MOTOR-CEMENG KALANG SIDOARJO - Pierre Patarianto (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2020)
This research aims to determine the path influence of variable analysis of service price, service quality, comfort and customer satisfaction. And know the most dominant variables in influencing the workshop business Delta Motor located in the area Cemengkalang Sidoarjo. The approach in this study used Expalnatory research with data collection methods and questionnaires with simple randomized sample research techniques there were 50 respondents. One data collection technique with questionnaires, surveys, polls, and observations, while the data captured is primary data and skunder data, while data analysis techniques using the Analysis Path (path analysis). The results showed that: 1) the influence of the service price variable to the comfort variable is 7.10. 2) The influence of service quality variables against the convenience satisfaction variable is 8.42. 3) The influence of price variables against customer satisfaction variables is 6.75. 4) The influence of variable comfort to consumer satisfaction is 20.91. 5) The influence of service quality variables to consumer satisfaction is 2.90.